Investigation of the biochemistry of post-translational modifications to Group VII ETHYLENE RESPONSE FACTORS - Zubrycka, Agata (2022)
In Arabidopsis thaliana the group VII ETHYLENE RESPONSE FACTOR (ERFVII) transcription factors (RAP2.12, RAP2.2, RAP2.3, HRE1, HRE2) have been shown to be substrates of the PLANT CYSTEINE OXIDASE (PCO) branch of PROTEOLYSIS (PRT6) N-degron pathway, that acts to regulate oxygen and nitric oxide sensing in plants. ERFVIIs share a conserved second position Cys motif, which is assumed to undergo posttranslational modifications in the presence of O2 and nitric oxide (NO). In the currently understood pathway Cys-2 is exposed following methionine cleavage by METHIONINE AMINOPEPTIDASES (MAPs) and undergoes oxidation by PCOs to Cys (SO2H), which allows subsequent arginylation by ARGININYL TRANSFERASEs (ATE). The amino terminal (Nt)-Arg residue is recognised by E3 ligase PRT6, leading to 26S proteasome degradation. The enzymatic components of the PCO N-degron pathway are oxygen and NO sensors and its substrates are transducers of the hypoxia or NO deficit. However, the exact chemical nature of Ntmodifications of pathway substrates, and in particular the oxidative state of Cys-2 are still under discussion and have not been investigated directly. In addition, NO affects the PCO N degron pathway at a yet to be identified point. Here the stability of ERFVIIs RAP2.3, HRE2 and HRE1 was studied in vivo in response to oxygen restricted conditions (submergence), in the presence of a 26S proteasome inhibitor (bortezomib) and in mutants of the PCO N-degron pathway. These analyses revealed an unexpectedly slower than predicted mobility of stable ERFVIIs during sodium dodecyl sulfate–polyacrylamide gel electrophoresis (SDS-PAGE). The possibility of post-translational modifications (PTMs) affecting the stability and size of RAP2.3 was investigated, including possible ubiquitin-like PTM addition. Studies of physiochemical properties related to amino acid composition responsible for the unexpected slower gel mobility were conducted in in vitro cell-free Wheat germ (WG) and Rabbit Reticulocyte (RR) lysates and with recombinant RAP2.3-6xHis produced in Escherichia coli. These analyses excluded the possibility of PTMs as a cause of the slower gel mobility of ERFVIIs. Results showed the direct influence of a highly hydrophobic amino acid composition in the C-terminal region of RAP2.3, on the gel mobility. The physiochemical reasons for this were investigated using bioinformatic tools.